2015
DOI: 10.15389/agrobiology.2015.2.198eng
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Growth Hormone, Growth Hormone Receptor, Prolactin and Prolactin Receptor Genes in Connection With Egg Production in Poltava Clay Chicken

Abstract: A b s t r a c tThe molecular assisted selection in animals is based on polymorphism study of desired gene alleles related to economic important traits, particularly productivity parameters. Allelic variants can be a result of different modification of DNA nucleotide composition, i.e. spot mutations leading to a single nucleotide polymorphism (SNP), insertions and deletions (indel), etc. Anyway, targeted selection necessitates detecting gene polymorphism and estimating its relationship with productivity. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…The growth hormone receptor (GHR) gene is located in the Z chromosome, (Zhang et al, 2016), which determines the hemizygous state in hens, thus there was no heterozygous AB in 90 Lien Minh hen individuals. The results of previous studies showed that the Ukrainian chicken Poltava Clay had genotype frequencies of A0 (0.28) and B0 (0.72) (Kulibaba et al, 2015) and Wenchang Chinese Chicken Breeds had genotypic frequencies of A0 (0.20) and B0 (0.80) (Li et al, 2008). However, in a study in the Mazandaran chicken, the results showed that the occurrence of genotype A0 (0.99) was significantly higher than that of genotype B0 (0.01) (Babak and Ghodrat, 2009).…”
Section: Genotypic and Allelic Frequenciesmentioning
confidence: 98%
“…The growth hormone receptor (GHR) gene is located in the Z chromosome, (Zhang et al, 2016), which determines the hemizygous state in hens, thus there was no heterozygous AB in 90 Lien Minh hen individuals. The results of previous studies showed that the Ukrainian chicken Poltava Clay had genotype frequencies of A0 (0.28) and B0 (0.72) (Kulibaba et al, 2015) and Wenchang Chinese Chicken Breeds had genotypic frequencies of A0 (0.20) and B0 (0.80) (Li et al, 2008). However, in a study in the Mazandaran chicken, the results showed that the occurrence of genotype A0 (0.99) was significantly higher than that of genotype B0 (0.01) (Babak and Ghodrat, 2009).…”
Section: Genotypic and Allelic Frequenciesmentioning
confidence: 98%
“…Бірківська барвиста -локальна яєчна порода курей, створена порівняно нещодавно на основі українських ліній леггорнів (Каталог, 2006; Шуплик та ін., 2013). Існуючі молекулярно-генетичні дослідження даних порід показують їх особливості за низкою ДНК-маркерів продуктивних ознак Kulibaba, 2015). Як виявлено у даному дослідженні, за локусом TLR4 зазначені породи також характеризуються чітко вираженими особливостями генетико-популяційних показників, що можна пояснити відмінностями у їхньому походженні та різним напрямом продуктивності.…”
Section: селекція і генетикаunclassified
“…Many genes have been used with the help of Molecular Markers to improve the productive performance of animals and this creates promising UTJagr opportunities for the development of genetic improvement programs and to obtain the best products with the help of genetic markers that have high accuracy in determining the Genetic Value of animals, and these methods provided opportunities for genetic improvement by increasing the growth rate and improving the quality of animals carcass ( Liu et al 2005) and finding cross-breeding programs that can be adopted in genetic improvement programs by direct selection of the desired traits to obtain the best production. The Pit-1 gene is one of the most important genes that have been nominated as a gene that contains multiple polymorphisms (SNPs) affecting growth and productive traits in domestic birds ( Kulibaba et al 2015). The role of the Pit-1 gene is essential for the production of growth hormone (GH) in the pituitary gland, meaning that the synthesis of growth hormone fails in its absence ( Harvey et al1998), ( Pfaffle et al1999), ( Wegner et al1993).…”
Section: Introductionmentioning
confidence: 99%